Poaching and illegal wildlife trade in western Argentina - Becerra, Sofía (2022)
Human-wildlife interactions, poaching and illegal wildlife trade in particular, are among the major threats to biodiversity around the world, causing species and population extinctions, zoonotic diseases dissemination, and exotic species invasions, among others. Here we assessed the patterns of poaching and illegal wildlife trade in western Argentina. We reviewed official infringement and verification records for 5 years (2015 to 2019) in San Juan province. We assessed the taxa involved and their conservation status, including wildlife uses and poaching elements. We found 58 taxa involved in 697 records. Most of them were birds (72%), followed by mammals (26%) and reptiles (2%). However, mammals are proportionally the most poached taxon in relation to their richness in the region. We detected that the bird Saltator aurantiirostris was the most prevalent species, appearing in 63% of all records, while Diuca diuca, the second most seized species, appeared in 19% of the infringement proceedings. This study shows that illegal hunting and trafficking are frequent activities affecting many species in the province, and that mammals and birds are the most affected taxa. Mammals were mostly involved in poaching events for their meat and fur, for which individuals were killed. On the other hand, birds were mainly live-captured to be sold as pets. Actions are necessary to protect fauna and raise people’s awareness in order to effectively control these illegal activities and support ecosystem health and integrity. To tackle these problems, it is fundamental to understand the impacts of poaching and trade, improve state control to prevent these activities, and employ non-formal education actions to change people’s behavior towards conservation.